2017
DOI: 10.1088/1361-6560/aa54f2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of undersampling and reconstruction algorithm dependence on respiratory correlated 4D-MRI for online MR-guided radiation therapy

Abstract: The purpose of this work is to investigate the effects of undersampling and reconstruction algorithm on the total processing time and image quality of respiratory phase-resolved 4D MRI data. Specifically, the goal is to obtain quality 4D-MRI data with a combined acquisition and reconstruction time of five minutes or less, which we reasoned would be satisfactory for pre-treatment 4D-MRI in online MRI-gRT. A 3D stack-of-stars, self-navigated, 4D-MRI acquisition was used to scan three healthy volunteers at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 29 publications
0
75
0
Order By: Relevance
“…Stemkens et al used a stack of stars trajectory to generate a respiratory correlated 4D-MRI with linear phase binning [7]. Several authors have also demonstrated the feasibility of an online constructed 4D-MRI using a stack of stars trajectory similar to the sequence presented here [7,22]. Online 4D-MRI using "pre beam" 4D-MRI and online 2D-cine has shown encouraging results [23].…”
Section: Discussionmentioning
confidence: 98%
“…Stemkens et al used a stack of stars trajectory to generate a respiratory correlated 4D-MRI with linear phase binning [7]. Several authors have also demonstrated the feasibility of an online constructed 4D-MRI using a stack of stars trajectory similar to the sequence presented here [7,22]. Online 4D-MRI using "pre beam" 4D-MRI and online 2D-cine has shown encouraging results [23].…”
Section: Discussionmentioning
confidence: 98%
“…It may be tempting to consider using the 4D-SOPI method to construct motion models for use in treatment planning (i.e., during MR simulation). While this is a possibility, higher quality 4D-MR images may be obtained with dedicated 3D approaches in shorter scan durations [17], [34]. The main benefit of 4D-SOPI is the simultaneous realtime imaging and construction of serial, self-navigated 4D-MR epochs for dose reconstruction for abdominal and thoracic MR-gRT.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the lesions will decrease the volume and hence registration time. The increasing use of image registration in different applications in the context of MR guided radiotherapy [33][34][35][36], registration algorithms capable of parallel computing [37] and the use of different parallel imaging reconstructions will lead to further time reductions [38]. The physician should decide if registration in case of expiration is necessary or not and if nn-Reg should be preferred because of shorter reconstruction times if image quality is supposed to be not significantly lower compared to dir-Reg Another requirement would be the same patient positioning in the CT and the MR to avoid inaccuracies in image fusion.…”
Section: Discussionmentioning
confidence: 99%